2019
DOI: 10.1101/544023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spastin tethers lipid droplets to peroxisomes and directs fatty acid trafficking through ESCRT-III

Abstract: Lipid droplets (LDs) are neutral lipid storage organelles that transfer lipids to various organelles including peroxisomes. Here, we show that the hereditary spastic paraplegia protein M1 Spastin, a membrane-bound AAA ATPase found on LDs, coordinates fatty acid (FA) trafficking from LDs to peroxisomes through two inter-related mechanisms. First, M1 Spastin forms a tethering complex with peroxisomal ABCD1 to promote LD-peroxisome contact formation. Second, M1 Spastin recruits the membrane-shaping ESCRT-III prot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 60 publications
(81 reference statements)
1
23
0
Order By: Relevance
“…The lumenal cavity of the copolymer was strongly positively charged and capable of shaping negatively charged membranes into positive-curvature membrane tubes in vitro and in vivo. Consistently, studies in living cells have shown that CHMP1B and IST1 co-localize with the VPS4 family member SPASTIN along the positive curvature surfaces of endosomal tubules and contact sites between lipid droplets and peroxisomes ( 10, 14, 15, 26 ). To better understand these new properties and roles for CHMP1B and IST1, and the still unknown structural mechanism by which any ESCRT-III protein interacts with lipid bilayers, we sought to understand how CHMP1B and IST1 work together to bind and constrict membranes.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The lumenal cavity of the copolymer was strongly positively charged and capable of shaping negatively charged membranes into positive-curvature membrane tubes in vitro and in vivo. Consistently, studies in living cells have shown that CHMP1B and IST1 co-localize with the VPS4 family member SPASTIN along the positive curvature surfaces of endosomal tubules and contact sites between lipid droplets and peroxisomes ( 10, 14, 15, 26 ). To better understand these new properties and roles for CHMP1B and IST1, and the still unknown structural mechanism by which any ESCRT-III protein interacts with lipid bilayers, we sought to understand how CHMP1B and IST1 work together to bind and constrict membranes.…”
Section: Introductionsupporting
confidence: 64%
“…First discovered for their role in the formation of multivesicular bodies (MVBs), ESCRT proteins serve essential functions in an expanding range of cellular processes. Beyond MVBs, these processes include: cytokinetic abscission; egress of enveloped viruses; sealing holes in nuclear, endosomal, and plasma membranes ( 19 ); and in peroxisome biogenesis and function ( 10, 11 ). ESCRT-III proteins primarily shape negatively-curved membranes, such as the necks of budding viruses or intralumenal vesicles, but we and others have shown that some ESCRT-III proteins can also stabilize positively-curved membranes ( 1215 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since lipid droplets are bounded by a phospholipid monolayer studded with cytosol-exposed proteins, tether proteins on juxtaposed organelles could either bind directly to the lipid droplet membrane via lipid-interacting domains (for example, the ER resident protein DGAT2, which binds the lipid droplet bilayer directly via its C-terminal domain), or via protein-protein interactions between the apposed membranes [ 26 ]. Information about the molecular identities of lipid droplet-peroxisome tethers is scarce, with the protein-protein interaction between the lipid droplet membrane-bound AAA ATPase M1 Spastin and the peroxisomal fatty acid transporter ABCD1 being the best characterised [ 178 ] ( Table 1 ; Fig. 2 ).…”
Section: Peroxisome-organelle Interactions and Their Physiological Rementioning
confidence: 99%
“…Moreover, M1 Spastin recruits ESCRT III proteins to remodel the lipid droplet membrane, facilitating fatty acid trafficking at these MCSs [ 178 ]. Interestingly, cumyl-OOH treatment, which induces lipid peroxidation and consequently oxidative stress, leads to an increase in the ABCD1-mediated contacts between lipid droplets and peroxisomes which might suggest an additional role of this peroxisome-lipid droplet MCS in redox homeostasis [ 178 ] ( Table 1 ; Fig. 2 ).…”
Section: Peroxisome-organelle Interactions and Their Physiological Rementioning
confidence: 99%
“…Beyond the biogenesis process, mature LDs remain in contact with the ER [19,20], allowing the transfer of lipids and proteins [21]. Contact sites with mitochondria [22,23] and peroxisomes [24] enhance fatty acid exchanges and modulate metabolic functions. These inter-organellar interactions suggest the existence of a finely tuned trafficking.…”
Section: Introductionmentioning
confidence: 99%